Remarks on fermion-boson equivalence in three dimensions - Dutra, Alvaro de Souza [UNESP]; Natividade, C. P. (World Scientific Publishing, 1999)
Starting from a decomposition of the self-dual field in (2 + 1) dimensions, we build up an alternative quantum theory which consists of a self-dual model coupled to a Maxwell-generalized Chern-Simons theory. We discuss the fermion-boson equivalence of this quantum theory by comparing it with the Thirring model. Using these results we were able to compute the mass of the bosonized fermions up to third order in 1/m. Some problems related to the number of poles of the effective propagator are also addressed.